Study of the physical and chemical characteristics of the Euphrates River in the Al-Fadhliah district in Nasiriya governorate - Prof. Dr. Kamel K. Fahd; Zaman M. Abdalwahad (University of Thi-Qar Journal of agricultural research, 2022)
The current study dealt with the study of physical and chemical characteristics to assess the environmental condition of the Euphrates River for the period from the 5th of September 2021 to the 5th of February 2022. The length of the Euphrates River is 2780 km from its branching point, the height of its source is 4500 m and the amount of water flowing in it is 818 square meters per second. Its source from (Turkey, Syria, Iraq), Gazi(2004). It pours into the Arabian Gulf, passing through several districts and sub-districts belonging to the Dhi Qar Governorate, and the Euphrates River is surrounded by vast agricultural lands planted with field crops and palms. Three stations were selected for the study. The first station is located 167 km north of the Fadhliah district in the water supply site for the region, the second station is located eight kilometers from the first station after crossing the river to the Fadhliah district. The third station is located 13 kilometers from the second station. The abiotic environmental characteristics such as air and water temperature, light transmittance, salinity, dissolved oxygen, carbon dioxide, pH, alkalinity, total hardness, and biological oxygen requirement were measured regularly for a period of six months. The water temperature ranged (from 20-12.5) in the first and third stations, respectively. The light transmittance ranged between (23-32) cm. The lowest values of salinity (1.5 parts per thousand) were recorded during November in the first station. The highest was (5.72) parts per thousand in the third station in January. The values of dissolved oxygen showed a decrease in the hot months (September and October), and the lowest values were (7.4) mg/liter during November in the second station. The pH ranged between (7.9-8.5), and the highest concentrations of the hardness of water were recorded in January (450 mg/L).